Families' perceptions of support from health care professionals in the three emergency departments in KwaZulu Natal, South Africa - W. Emmamally; P. Brysiewicz (Elsevier, 2019)
Purpose: The purpose of this study was to investigate families' perceptions of support provided by health care professionals in three emergency departments in KwaZulu-Natal, South Africa. Background: In low- and middle-income countries, engagement with families in emergency departments is often aimed at supplementing manpower for care provision rather than supporting the family. There does, however, need to be appropriate family support, provided through ongoing collaboration and capacity-building with the family. Design and methods: A quantitative survey of 353 family members of patients admitted to emergency departments was conducted in three emergency departments in the province of KwaZulu-Natal, South Africa. A well validated instrument, the Iceland-Family Perceived Support Questionnaire, was used to collect data on family perceptions of cognitive and emotional support received from health care professionals in the emergency department. Mean scores for overall family support, and cognitive and emotional support subscales were calculated. Results: Family members gave significantly lower scores average for perceived cognitive and emotional support (8.7; 14.5) respectively, as compared to other studies using the same questionnaire. The mean overall support score for the questionnaire was (22.3, sd 12.4). Conclusions: Families perceived significantly lower overall support from health care professionals in the emergency department as compared to the findings of international studies using The Iceland-Family Perceived Support Questionnaire. Although emergency care settings can be very busy, health care professionals need to engage with families to provide appropriate support in order to enhance families' ability to cope effectively. Keywords: Emergency department, Families, Iceland-Family Perceived Support Questionnaire